2016
DOI: 10.3390/ma9040279
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Pt/Ti/TiO2 Photoelectrodes by RF-Magnetron Sputtering for Separate Hydrogen and Oxygen Production

Abstract: Evolution of pure hydrogen and oxygen by photocatalytic water splitting was attained from the opposite sides of a composite Pt/Ti/TiO2 photoelectrode. The TiO2 films were prepared by radio frequency (RF)-Magnetron Sputtering at different deposition time ranging from 1 up to 8 h and then characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and ultraviolet-visible-near infrared (UV-vis-NIR) diffuse reflectance spectroscopy. The photocatalytic activity was evaluated by incident photon to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…Provided that good electrical contact could be established between the support and the catalyst and between the catalytic material, the electrical polarization of the catalyst prevents electron-hole recombination, potentially compensating the inherent lack of surface area. TiO 2 photoactive coatings can be obtained by several techniques, such as sol-gel, chemical vapor deposition, radio frequency magnetron sputtering, plasma spray, electron beam evaporation, pulsed laser deposition, anodic oxidation and plasma electrolytic oxidation (PEO) [28][29][30][31][32][33]. Among them, electrochemical anodization allows the direct growth of the photoactive catalyst by oxidation of an electrically conducting support (e.g., a titanium mesh) providing good mechanical adhesion and electrical contact with the substrate [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Provided that good electrical contact could be established between the support and the catalyst and between the catalytic material, the electrical polarization of the catalyst prevents electron-hole recombination, potentially compensating the inherent lack of surface area. TiO 2 photoactive coatings can be obtained by several techniques, such as sol-gel, chemical vapor deposition, radio frequency magnetron sputtering, plasma spray, electron beam evaporation, pulsed laser deposition, anodic oxidation and plasma electrolytic oxidation (PEO) [28][29][30][31][32][33]. Among them, electrochemical anodization allows the direct growth of the photoactive catalyst by oxidation of an electrically conducting support (e.g., a titanium mesh) providing good mechanical adhesion and electrical contact with the substrate [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Processing times required to obtained crystalline films are of the order of only few minutes (less than 10 min) and the resulting films show a peculiar porous double-layered morphology [37]. Some of the authors recently reported that TiO 2 films obtained by PEO outperform TiO 2 nanotube arrays showing quantum yields higher than 90% in photon-to-electron conversion [32,38]. They also demonstrated that TiO 2 films obtained by PEO are effective in water decolourization by photoelectrocatalysis [39] and that the catalysts can be successfully reused several times and regenerated if necessary [40].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its nontoxicity, low cost, good chemical stability, and band energy levels suitable for excitation under UV–vis irradiation, titanium dioxide and its doped variants are considered among the most viable electrode materials for photocatalytic applications, such as water and air depollution, water splitting and CO 2 reduction. [ 1–8 ] Out of all techniques for the growth of thin films for photoelectrodes preparation, [ 9–11 ] Plasma Electrolytic Oxidation (PEO) allows to easily synthesize photoactive TiO 2 layers with tuned crystalline phase composition [ 12–14 ] and dosage of doping elements. [ 15–21 ]…”
Section: Introductionmentioning
confidence: 99%
“…Considering the above precedents and the visible-light photocatalytic activity for independent hydrogen and oxygen generation using Au/TiO 2 or Au/CeO 2 , respectively, in the presence of an appropriate sacrificial agent, it occurs that these two photocatalysts could also work in a system to perform the simultaneous generation of hydrogen and oxygen in the absence of sacrificial agents using a Z-scheme [25][26][27][28]. In this Z-scheme methodology, hydrogen and oxygen are generated photocatalytically in different cells that are irradiated and separated by a membrane [5,[29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%